Perlindungan Sakramentalitas Perkawinan Katolik di Era Pornografi: Tinjauan Kanon 1055–1101 dan Implikasi Pastoral bagi Pasangan Dewasa Muda - Nona, Tryepina Paulina; Suwul, Karolina (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The contemporary digital era has triggered the normalization of pornography and promiscuous sexual behavior, which significantly threatens the theological understanding and sacramental practice of Catholic marriage among young adults. This article aims to examine, from a theological-juridical perspective, how canons 1055–1101 of the Code of Canon Law (CIC) serve as the authoritative foundation for the Church in safeguarding the dignity and validity of the sacrament of marriage. The method employed is a comprehensive literature study of the CIC, relevant magisterial documents of the Church, and contemporary scholarly works on the dynamics of young adult relationships. The concise findings indicate that exposure to and normalization of pornography directly weaken three fundamental aspects of Catholic marriage, namely the capacity to give free consent, the intention to practice permanent fidelity, and the correct understanding of the body’s meaning as a total self-gift. Nevertheless, the Church possesses solid canonical and pastoral instruments to address these challenges and facilitate restoration. In conclusion, a synergistic integration of canonical approaches, moral teachings, and pastoral guidance is required to assist young adult couples so that they may realize marriages that are not only canonically valid but also psychologically mature and sacramentally holy.